Human factors in the adoption of M-learning by COVID-19 frontline learners - Ebardo, Ryan A. (Animo Repository, 2021)
Mobile Learning is crucial to the continuity of healthcare education during COVID-19. Despite its penchant for the traditional delivery of course content through classroom and clinical settings, M-Learning proved to be a viable solution in a pandemic due to social isolation, community restrictions, and safety concerns. We invited 219 frontline learners from 3 universities, active healthcare professionals who are currently enrolled, to test a structural model based on the Theory of Reason Action. We positioned the human factors of cognitive, social, and affective needs as determinants of attitude in the behavioral intention to adopt M-Learning. We further hypothesize that social norms positively influence the behavioral intention to adopt M-Learning among healthcare frontliners. We applied PLS-SEM to analyze the survey data and revealed that human factors positively influence attitude, leading to the behavioral intention to adopt M-Learning. Social norms and their influence on the behavioral intention to adopt this technology are not supported. We discuss the implications of our study, acknowledge its limitations while mapping out directions for future works to understand M-Learning adoption further.